2012
DOI: 10.1111/j.1475-1305.2012.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three‐dimensional embedded strain transducers, compression tested within the same strain field while offset at an angle with the principal axes

Abstract: The strain tensor and principal strains were derived for a range of different patterns of three‐dimensional strain transducers. The precisions of the estimates of these values were based on the Monte Carlo simulation applied to experimental work that was conducted on strain transducers tested within the same strain field. The estimates of precision were also determined theoretically and compared with results based on experimental findings. Results suggest that the tetrahedron transducers in experimental work d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Their field of application depends mainly on the material under consideration. There have been attempts at using embedded strain gauges but mostly, the techniques rely on non‐contact volume imaging of deformation from a number of different physical information. In materials that exhibit a magnetic resonance imaging signal (mainly biological materials with high water content), magnetic resonance elastography provides high quality bulk deformation data .…”
Section: Introductionmentioning
confidence: 99%
“…Their field of application depends mainly on the material under consideration. There have been attempts at using embedded strain gauges but mostly, the techniques rely on non‐contact volume imaging of deformation from a number of different physical information. In materials that exhibit a magnetic resonance imaging signal (mainly biological materials with high water content), magnetic resonance elastography provides high quality bulk deformation data .…”
Section: Introductionmentioning
confidence: 99%
“…This selection of transducer is consistent with results from other research using the orthogonal transducers shown in Figure , since in an analysis carried out by O'Driscoll et al . , these orthogonal patterns produced the best overall estimates of strain at an internal point with the majority of the theoretical values falling within the range of the experimental results.…”
Section: Methods Used In Relation To Research Carried Out On a Prosthmentioning
confidence: 52%
“…The transducers of Figure B (v and vi) are made in a similar way except that individual gauges (usually Kyowa type KFG‐1N‐120‐C1‐11N30C2) are mounted on the faces of the miniature tetrahedrons (see Figure B (vii)), using special purpose instrumentation described by O'Driscoll et al . . These are much more difficult to manufacture than the previous type of rosette since each individual gauge has to be aligned with the sides of the tetrahedron.…”
Section: Introductionmentioning
confidence: 99%
“…With a ¼ Wheatstone bridge it is necessary two or three wires (in this case it is possible to assess wire resistance), but the strain signal reduces to a quarter of the full bridge measured. However, the strain gauge sensor represents a highly tested, mature and overspread technology, offering good sensitivity, precise measurements and competitive price [13,14] . In addition, noise patterns and high sensitivity to moment of force in large COP displacements suggest the use of more than one load cell tube [8,21] , as this is due to the central extrapolation nature of the measurement accomplished with this type of single load cell.…”
Section: Discussionmentioning
confidence: 99%
“…Piezoelectric sensors require a specific signal-conditioning device known as a charge amplifier [13] . The strain gauge is bonded on the surface of a mechanical structure whose geometry definition (among several sensor topologies that have been used [14][15][16] ) impacts in the force plate project and the final selected topology should be based on simplicity and robustness criteria [16] .…”
mentioning
confidence: 99%